Developing digital platform to assess interests and talents at senior high school students - Nanda Savira Ersa; Zara Yunizar; Nura Usrina; M Fauzan; Misbahul Jannah; Isna Rezkia Lukman; O.K. Muhammad Majid Maulana; Ditya Larasati Putria (Universitas Muhammadiyah Malang, 2025)
In today's digital era, fostering students' interests and talents is important. This study addresses the challenge of students struggling to identify and develop their potential, hindering their character development and limiting their success in a digitally connected world. This activity aimed to develop a digital platform to optimize student potential by providing personalized recommendations based on established assessment methods: Holland's RIASEC and Multiple Intelligence System (MIS). Conducted at SMAN 1 Lhokseumawe with 50 student participants, the project involved observation, website development, socialization, and ongoing refinement. The developed website provides students with personalized assessments and extracurricular recommendations, while also offering management tools for teachers, school operators, and the principal. Initial surveys revealed that while students were interested in extracurricular activities, many lacked clarity regarding their talents and the alignment of those talents with their chosen activities. It is expected that this digital tool will not only enhance student self-awareness and character development but also contribute to improved student achievement and school branding, ultimately preparing students for success in the evolving digital landscape.